Source reconstruction via deposition measurements of an undeclared radiological atmospheric release - S. Van Leuven; S. Van Leuven; S. Van Leuven; P. De Meutter; P. De Meutter; J. Camps; P. Termonia; P. Termonia; A. Delcloo; A. Delcloo (Atmospheric Chemistry and Physics)
Inverse modelling of atmospheric releases of radioactivity consists of reconstructing the release source by combining radiological field measurements with atmospheric transport calculations. This is typically performed with air concentration measurements, although deposition measurements or gamma dose rate measurements could also be used. In this paper, we assess the use of deposition measurements of radioactivity in this context. This is done through a case study of the undisclosed release of the radionuclide 106Ru in Eurasia during the autumn of 2017. The atmospheric transport model we utilize for this purpose is FLEXPART. Inverse modelling is performed with the inverse modelling tool FREAR (Forensic Radionuclide Event Analysis and Reconstruction), which has been modified to work with deposition measurements. The inversion consists of Bayesian and cost-function-based algorithms to reconstruct the initial source properties. Inverse modelling is applied to both real and synthetic-deposition data following the 106Ru release. We also construct synthetic air concentration data for use in inverse modelling to make a comparison with the results using deposition data. It is found that source localization is feasible with both the synthetic and real-world deposition data. Synthetic air concentration measurements lead to more precise source localization than deposition. It is demonstrated that this can be explained by the lower detection limits of air concentration measurements compared to deposition.